2014
DOI: 10.14710/jitaa.39.3.180-187
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF SILKWORM PUPAE (Bombyx mori) MEAL TO SUBSTITUTE FISH MEAL ON PRODUCTION AND PHYSICAL QUALITY OF QUAIL EGGS (Cortunix cortunix japonica)

Abstract: Tujuan penelitian ini adalah untuk mengetahui efek substitusi protein tepung ikan dengan tepung pupa ulat sutera (Bombyx mori) terhadap performa produksi dan kualitas telur pada puyuh. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan empat perlakuan dan empat ulangan dengan sepuluh ternak tiap ulangan. Perlakuan yang diberikan adalah R0: pakan mengandung 8% tepung ikan, tanpa tepung pupa ulat sutera (kontrol), R1: pakan mengandung tepung pupa ulat sutera menggantikan 25% protein tepung ikan, R2: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…Overall, the weight of eggshell is affected by the cricket meal treatment. The average eggshell weight in this study is similar to a result reported by Rahmasari et al (2014). In this study, cricket meal treatment had significant effect on decreasing eggshell thickness.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the weight of eggshell is affected by the cricket meal treatment. The average eggshell weight in this study is similar to a result reported by Rahmasari et al (2014). In this study, cricket meal treatment had significant effect on decreasing eggshell thickness.…”
Section: Discussionsupporting
confidence: 90%
“…An important factor of quail production is a good maintenance management, including the availability of feed. Feed availability must be guaranteed in terms of quality, quantity, and continuity (Rahmasari et al, 2014). In the livestock industry, feed is a major cost factor.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the highest growth rate was observed in Clarias gariepinus fingerlings when fed with a diet containing a high level of silkworm pupae (Olaniyi and Babasanmi, 2013). Rahmasari et al (2014) found that the diet containing silkworm pupae had better growth performance. Tomotake et al (2010) reported that the silkworm pupae are good sources of high-quality protein in fishes.…”
Section: Growth Parametersmentioning
confidence: 85%
“…Hal tersebut menunjukkan bahwa penambahan tepung pupa ulat sutera tidak memberikan dampak negatif pada total konsumsi ransum. Rahmasari et al (2014) secara fisik (tekstur dan warna) dari tepung pupa ulat sutera hampir sama dengan tepung ikan. Selain itu, aromannya juga mempunyai kesamaan dengan tepung ikan.…”
Section: Biaya Produksiunclassified